Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.3748/wjg.15.204
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of vacA, cagA and babA2 genes in Cuban Helicobacter pylori isolates

Abstract: and seven isolates (82.3%) were babA2 -positive. A significant correlation was observed between vacAs1m1 a n d c a g A a n d b e t w e e n va c A s 1 m 1 a n d b a b A 2 genotypes (P < 0.001 and P < 0.05, respectively) and between babA2 genotype and cagA status (P < 0.05); but, no correlation was observed between vacAs1 and babA2 genotypes. Eighty five (65.4%) and 73 (56.2%) strains were type 1 (vacAs1 -cagA -positive) and "triplepositive" (vacAs1 -cagA -babA2 -positive), respectively, and their presence was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
64
10
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 40 publications
17
64
10
1
Order By: Relevance
“…Our data, however, supports the relationship between the genes cagA, cagE, vacA and babA2 that was described in previous reports [34][35][36][37] .…”
Section: Discussioncontrasting
confidence: 42%
“…Our data, however, supports the relationship between the genes cagA, cagE, vacA and babA2 that was described in previous reports [34][35][36][37] .…”
Section: Discussioncontrasting
confidence: 42%
“…The CagA seropositivity (60.6%) obtained with Helicoblot 2.1 test in this study was similar to the positivity observed in CagA genotyping of Western strains (24) and slightly lower than the cagA positive strains detected in Cuban H. pylori isolates (25). The Western blot assay with the rCagA developed here demonstrated adequate performance in comparison to HB 2.1 that contains the entire CagA antigen.…”
Section: Discussionsupporting
confidence: 81%
“…A total of 95 cagA positive H. pylori strains were isolated from antrum biopsies in a previous study involving 130 consecutive patients (77 male and 53 female) with a mean age of 49.1 (range 18 to 88) who underwent routine endoscopy due to dyspeptic complaints at CIMEQ Hospital, Havana, Cuba (22). Patients were classified in three groups (40 with duodenal ulcer, 19 with gastric ulcer, and 36 with non-ulcer dyspepsia) according to endoscopic and histological observations.…”
Section: Patients and H Pylori Isolatesmentioning
confidence: 99%
“…Genomic DNAs of the strains were extracted by CTAB method with phenol/chloroform and isopropanol precipitation as previously described (22). Purified DNAs were stored at -20ºC until use.…”
Section: Dna Extraction and Pcr Amplificationmentioning
confidence: 99%
See 1 more Smart Citation